2021
DOI: 10.1111/aos.14982
|View full text |Cite
|
Sign up to set email alerts
|

Vascular biomarkers from optical coherence tomography angiography and glaucoma: where do we stand in 2021?

Abstract: Biomarkers of ocular blood flow originating from a wide variety of imaging modalities have been associated with glaucoma onset and progression for many decades. Advancements in imaging platforms including optical coherence tomography angiography (OCTA) have provided the ability to quantify vascular changes in glaucoma patients, alongside traditional measures such as retinal nerve fibre layer thickness and optic nerve head structure. Current literature on vascular biomarkers, as measured by OCTA, indicates sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…OCT-A scans from macular and ONH scans in glaucoma have been shown to display good reproducibility, which supports the use of OCT-A longitudinally as well ( 73 ). Vessel density parameters have also been associated with visual field progression ( 74 , 75 ).…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…OCT-A scans from macular and ONH scans in glaucoma have been shown to display good reproducibility, which supports the use of OCT-A longitudinally as well ( 73 ). Vessel density parameters have also been associated with visual field progression ( 74 , 75 ).…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Optical coherence tomography angiography (OCTA) allows simultaneous assessments of retinal and optic nerve head (ONH) structure and vascular densities (VD), providing clinicians an improved user interface for the potential inclusion of vascular biomarkers [ 2 ]. Since its introduction, OCTA data from a wide range of studies have suggested a significant reduction in the mean peripapillary VD in glaucoma patients, as well as marked reduction in VD in the ONH and parafoveal regions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction, OCTA data from a wide range of studies have suggested a significant reduction in the mean peripapillary VD in glaucoma patients, as well as marked reduction in VD in the ONH and parafoveal regions [ 3 ]. The associations of OCTA VD outcomes and OAG are generally strong, suggesting lower VD of the peripapillary retina, ONH and macular regions in glaucoma patients when compared to healthy controls [ 2 , 3 ]. A recent study in a Chinese population found that significant microvascular damage assessed by OCTA was present in both macular and peripapillary regions in early OAG patients, with VD loss highest in peripheral regions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that parameters including blood flow density, blood flow index, and vessel density (VD) in the optic nerve head (ONH), peripapillary vascular layer, and macula decrease significantly in patients with glaucoma [ 7 14 ]. Furthermore, the decreased ocular blood flow (OBF) is closely related to the occurrence and development of glaucomatous optic neuropathy.…”
Section: Introductionmentioning
confidence: 99%